Characteristics of environmental Ribeirão Morangueiro Valley fund in Maringá city - PR - Fabiche, Mariana Natale Fiorelli; Alencar, José Luciano Sobreira de; Simoni, Júlio Henrique; Angelis Neto, Generoso de; Okawa, Cristhiane Michiko Passos (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
Maringá city is such as national referee when the subjects mean green and urban landscaping, due to the developing process, which is regarded to harmonic integration in urban areas environmental issues. However, there are degradation problems in some preservation areas, which can be found at perimeter of the city and it should be analyzed and the issue can be solved, for instance, preventive actions which can be taken to avoid any damage. This study aims to characterize the valley bottom of RibeirãoMorangueiro, which is affected by human actions as well as identifying issues related to erosion process, rainwater drainage, waste water, solid wate disposal, vegetation cover and environmental situation. The research was done by observations in local, recorded with photographies and samples of waste water were collected. By the way, this local present environmental irregulations such as erosion process, improper disposal of solid waste by the population, invasive plant species like leucaena discontinuities in land cover and irregularities in the stream factors, other problems such as water contamination and soil degradation affecting the environmental balance and health of the surrounding population. Regarding to described above, it is evident the need for preventive measures that seek to revitalize the MorangueiroRibeirão, as well as contribute to the preservation of the present study area.